2020
DOI: 10.1016/j.conbuildmat.2020.120193
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of a balsa wood veneer structural sandwich core material

Abstract: Balsa wood is an appropriate core material for structural sandwich applications due to its high strength-and stiffness-to-weight ratios. However, the mechanical properties vary considerably owing to the inherent scattering of natural wood materials. One approach to reduce this scatter and tailor the mechanical properties according to specific application needs is to recompose the natural material into a veneered material consisting of veneer layers of different grain orientations, which are adhesively bonded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…The Brinell hardness of the three wood species had values corresponding to the values reported in other research studies in the field [38,39]), but there were also small differences between them. For example, the Brinell hardness of balsa wood was only 22.8% lower than that of paulownia wood, although the density difference between the two wood species was 74.4%.…”
Section: Discussionsupporting
confidence: 80%
“…The Brinell hardness of the three wood species had values corresponding to the values reported in other research studies in the field [38,39]), but there were also small differences between them. For example, the Brinell hardness of balsa wood was only 22.8% lower than that of paulownia wood, although the density difference between the two wood species was 74.4%.…”
Section: Discussionsupporting
confidence: 80%
“…Shir Mohammadi et al [46], for example, demonstrated that laminated veneer lumber (LVL) balsa improved the toughness of a core material compared to solid balsa, although it is dependent on the lamination adhesive. Wu et al [47] similarly confirmed the advantage of using veneered balsa wood in comparison to block material, since the first one reduces property scatter. Nowadays, veneer-based core materials are commercially available as Baltek ® VBC from 3A Composites.…”
Section: Sustainable Coresmentioning
confidence: 81%
“…The end-grain balsa panels from Ecuador's shear characteristics show the influence of the density, adhesive connections and shear plane on the shear characteristics of the balsa panels. The balsa's density grew along with its shear stiffness and strength [13]. Due to plastic deformations in the tracheid, certain specimens showed notable ductility.…”
Section: Wood Corementioning
confidence: 99%